Reinventing and multiplying 'Comorian diaspora' within popular culture: Marseilles as 'diaspora space'. Issue 2 (1st October 2015) - Englert, Birgit; Fritsch, Katharina
Popular culture is an important domain in which postcolonial notions of diaspora are being negotiated. In this article, we focus on Marseilles, France, and the Comorian diaspora that currently represents one of the city's major migrant populations. More precisely, we focus on the talent show Étoiles Rasmi (2013) as well as the oeuvre by Franco-Comorian slam artist Ahamada Smis. While situated in different spheres of popular culture, Étoiles Rasmi as well as Ahamada Smis' artistic work hinge on shared 'diaspora spaces'. We will point out how both aim(ed) at inscribing notions of Comorian culture into a broader cultural market in Marseilles and argue that both contribute to a renegotiation of the postcolonial and intersectional power relations that have been shaping notions of Comorian diaspora in Marseilles. Two categories in particular come to be negotiated in this context: generation and ethnicity. In this article, we thus situate Étoiles Rasmi as well as Smis' work within positionalities of 'younger generations' of a 'Comorian diaspora' in Marseilles. In this regard both can be understood as reinventing or re-performing 'Comorian culture', affirming the role of notions of 'ethnicity' with respect to constructions of 'diaspora'.